ASPEK SEMANTIS DAN MORFOLOGIS PREFIKS PEMBENTUK VERBA DALAM BAHASA JERMAN - Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2017)
A discussion about the semantic and morphological aspects of prefixed verbs in German gives the learners an insight into a better understanding how they use those forms correctly in a sentence. The discussion also allows the German teachers to provide more detailed information about German grammar. In general, theoretical approaches used in studying the prefixed verbs are within the scope of synchronic and diachronic morphology.